1988
DOI: 10.1590/1809-43921988183315
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Atta (Hymenoptera - Formicidae) in "terra-firme" rain forest of Central Amazonia: density, species composition and preliminary results on effects of forest fragmentation

Abstract: SUMMARYOtic hundfiad and ^ounteen hectaAeA o{, a "teAAa-^iAti\z" Ααλη jotMt 70 fem noAth o& Ma-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 5 publications
(5 reference statements)
2
24
0
Order By: Relevance
“…Wint (1983), for instance, reported that Atta was responsible for as much as 80% of the leaf damage in the canopy of the Panamanian forest he studied. In contrast, leaf-cutting ants are extremely rare in some parts of Amazonia and Venezuela, particu larly in the primary forest (Vasconcelos, 1988;Jaffe & Villela, 1989), although when forest is cleared and the area left to regrowth, ant nest densities increase substantially (Vasconcelos & Cherrett, 1995). Such an increase may result from changes in abiotic conditions, particularly in creased light, since Atta nests appear to develop poorly in shady conditions (Jaffe & Vilella, 1989;pers.…”
Section: Introductionmentioning
confidence: 99%
“…Wint (1983), for instance, reported that Atta was responsible for as much as 80% of the leaf damage in the canopy of the Panamanian forest he studied. In contrast, leaf-cutting ants are extremely rare in some parts of Amazonia and Venezuela, particu larly in the primary forest (Vasconcelos, 1988;Jaffe & Villela, 1989), although when forest is cleared and the area left to regrowth, ant nest densities increase substantially (Vasconcelos & Cherrett, 1995). Such an increase may result from changes in abiotic conditions, particularly in creased light, since Atta nests appear to develop poorly in shady conditions (Jaffe & Vilella, 1989;pers.…”
Section: Introductionmentioning
confidence: 99%
“…Results from the BDFFP suggest that such sample effects could be especially important for Amazonian species, which often have patchy distributions at varying spatial scales and complex patterns of endemism (e.g., Zimmerman and Bierregaard 1986, Vasconcelos 1988, Allmon 1991, Rankin-de Merona et al 1992, Souza and Brown 1994, Didham et al 1998a, Laurance et al 1998a, Peres 2005. Pronounced clumping means many species will be missing from any particular fragment or reserve simply because they never occurred there in the first place.…”
Section: Sample Effectsmentioning
confidence: 99%
“…The acidic, nutrient-poor soils prevalent in much of Amazonia (Brown 1987) appear to promote animal rarity by limiting fruit and flower production and reducing the nutrient content of foliage (reviewed in Laurance 2001). As a result, many invertebrates (Vasconcelos 1988, Becker et al 1991 and vertebrates (Emmons 1984, Rylands and Keuroghlian 1988, Kalko 1998, Stouffer and Bierregaaard 1995a, Spironello 2001) are considerably less abundant in forests overlaying nutrient-poor Amazonian soils than they are in more-productive areas of the Neotropics. Intrinsic rarity is a critical feature, as demonstrated by studies of Amazonian trees.…”
Section: Sample Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…many species of large mammals [Lovejoy et al, 1986], primates [Gilbert and Setz, 2001], understory birds [Stouffer andBierregaard, 1995a;Stratford and Stouffer, 1999], and even certain beetle, ant, bee, termite, and butterfly species [Powell and Powell, 1987;Vasconcelos, 1988;Klein, 1989;Souza and Brown, 1994;Brown and Hutchings, 1997;Didham, 1997]. Many species that decline in fragments are sensitive to edge effects, including numerous flies, bees, wasps [Fowler et al, 1993], beetles [Didham, 1997], ants [Carvalho and Vasconcelos, 1999], and butterflies [Brown and Hutchings, 1997].…”
Section: )mentioning
confidence: 99%